2021
DOI: 10.3390/biomedicines9020125
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium, Little Known But Possibly Relevant: A Link between NASH and Related Comorbidities

Abstract: Non-alcoholic steatohepatitis (NASH) is characterized by an abnormal hepatic lipid accumulation accompanied by a necro-inflammatory process and a fibrotic response. It comprises from 10% to 30% of cases of patients with non-alcoholic liver disease, which is a global health problem affecting around a quarter of the worldwide population. Nevertheless, the development of NASH is often surrounded by a pathological context with other comorbidities, such as cardiovascular diseases, obesity, insulin resistance or typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 81 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…In addition to, it has been found that reduced levels of magnesium ions in serum and liver lead to reduced mitochondrial function in the body, metabolic disorders, oxidative stress and inflammatory responses thus leading to liver-related diseases [ 29 ]. It was found that magnesium ion deficiency can lead to increased blood lipid levels as well as exacerbate lipid deposition in the liver [ 30 ]. Majid et al revealed that magnesium supplementation had an ameliorating effect on the levels of ALT and AST, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to, it has been found that reduced levels of magnesium ions in serum and liver lead to reduced mitochondrial function in the body, metabolic disorders, oxidative stress and inflammatory responses thus leading to liver-related diseases [ 29 ]. It was found that magnesium ion deficiency can lead to increased blood lipid levels as well as exacerbate lipid deposition in the liver [ 30 ]. Majid et al revealed that magnesium supplementation had an ameliorating effect on the levels of ALT and AST, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The inefficient hepatic blood transfer that occurs with aging exacerbates the reduction in liver size, and the transport of lipoproteins and carbohydrates has also been reported to be altered. Magnesium has been described to correlate inversely with the quality of circulating carbohydrates [ 98 ], and a relationship between the cation and insulin secretion and insulin resistance (IR) has been recently studied by our group [ 5 ]. Almost 50% of patients with type 2 diabetes mellitus (T2DM) suffer from hypomagnesemia, mainly caused by low intake and increased urinary loss of magnesium [ 99 ].…”
Section: Aging and Magnesium Alterations: Trigger Or Consequence?mentioning
confidence: 99%
“…Hepatocyte physiology is also altered; polyploidy and accumulation of dense bodies [ 95 ], together with increased lipid content [ 101 ] and impaired metabolic pathways such as glycolysis [ 102 ], β-oxidation [ 103 ], autophagy, energy sensing, and circadian rhythms [ 104 ], are characteristic of aged hepatocytes. In this context, our group has reported that magnesium modulates the lipid content of the liver [ 5 ], and its role as a cofactor in energy-processing enzymes may prevent age-related energetic impairment. Similarly, magnesium plays a role in preventing the activation of KCs [ 105 ] and the production of alpha-smooth muscle actin by hepatic stellate cells (HSC) [ 106 ].…”
Section: Aging and Magnesium Alterations: Trigger Or Consequence?mentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary imbalances are increasingly recognized as the root cause of NASH-related comorbidities and Simón et al [ 10 ] describe in this Special Issue that a deficit in magnesium, a micronutrient found in most green vegetables, legumes, peas, beans and nuts, might aggravate NASH and its related diseases. The authors characterized the potential role that magnesium might play in the development of liver diseases and metabolic syndrome.…”
mentioning
confidence: 99%